2005
DOI: 10.1080/02813430510031306
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ reported reasons for avoiding MMR vaccination

Abstract: Postponers and abstainers may have different reasons for their decision. The role of well-trained healthcare staff in giving advice and an opportunity to discuss MMR vaccination with concerned parents is very important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 13 publications
0
57
1
2
Order By: Relevance
“…The findings suggest primary health care providers (72.3%), schools (24%), and television (22.3%) as the important sources of information while in developed countries, the media was a leading source of information about childhood vaccinations (16). Accordingly, results demonstrated that most children were vaccinated at health centers and schools.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The findings suggest primary health care providers (72.3%), schools (24%), and television (22.3%) as the important sources of information while in developed countries, the media was a leading source of information about childhood vaccinations (16). Accordingly, results demonstrated that most children were vaccinated at health centers and schools.…”
Section: Discussionmentioning
confidence: 71%
“…In the current study, the main obstacles for lack of vaccination were refusal to vaccinate (31%), lack of information (24.2%), sick child (22.4%), and travel (20.2%). However, in most studies, fear of vaccine side effects was the leading barrier to vaccination (1,12,13,(15)(16)(17). In a study from the United Kingdom, fever, rash, joint symptoms, and headache were reported as vaccine side effects (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many, including health care workers, the main source of information about disease, terrorism, and vaccines is the mass media, followed by health centers and professionals [52,53]. Both national and local media networks, such as television and radio, are important information sources in the event of a bioterrorist incident [54].…”
Section: Crisis Communication For Effective Smallpox Vaccinationmentioning
confidence: 99%
“…Many of these children were too young to be vaccinated, unable to receive them for medical reasons or contracted disease as a result of vaccine failure. However, some parents choose not to vaccinate their children, citing political, personal or philosophical motives for declining [9][10][11][12]. Other vaccine opponents question the safety, efficacy and necessity of recommended vaccines [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%